Kajian pengendalian waktu dan biaya dengan metode nilai hasil dan simulasi monte carlo - Rahmayana, Rahmayana; Bachmid, Sofyan; Maricar, Husni (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
It is not uncommon for a project to be built to experience deviations, either in terms of time exceeding the plan, or implementation costs increasing beyond the project's Implementation Budget Plan (RAP). In this research, namely the renovation and relocation project of Bank Mandiri Malino sub-branch office, Gowa Regency, it is deemed necessary to control costs and time using the value of results and Monte Carlo concept methods to overcome all risks of uncertainty that affect project delays, cost and time performance and value. probability of accuracy of costs and time in the construction of the project. The value concept results from analyzing the Planned Cost Budget (RAB), prices of wages and materials as well as actual project costs. Then, using the Monte Carlo method, analyzes the varying cost and time ranges obtained from interviews with contractors. Analysis carried out by comparing manual calculations and using monitoring software based on the value of results concept method shows that the estimated project completion costs 1,375,951,311.10 with a project duration of 146 days. Meanwhile, the cost of completing the project based on Monte Carlo simulation is 1,608,123,328.80 with a completion time of 130 days.